2013
DOI: 10.3748/wjg.v19.i20.3165
|View full text |Cite
|
Sign up to set email alerts
|

Behçet’s disease complicated by multiple aseptic abscesses of the liver and spleen

Abstract: Aseptic abscesses are an emergent entity and have been described in inflammatory bowel disease, especially in Crohn's disease, and in other diseases. However, aseptic abscesses associated with Behçet's disease are extremely rare. We report a Japanese male diagnosed with an incomplete type of Behçet's disease who developed multiple aseptic abscesses of the spleen and liver. In 2002, the spleen abscesses were accompanied by paroxysmal oral aphthous ulcers and erythema nodosum. As the patient's response to antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Aseptic liver abscesses have been described in inflammatory bowel disease, particularly Crohn's, but are rare in systemic inflammatory conditions [9]. Maeshima et al reported a case of aseptic abscesses in a patient with Behcet's disease that improved with corticosteroid therapy [10,11]. The diagnosis of Behçet's was considered based on her reported painful oral and vaginal lesions but similar lesions in SLE have also been reported [12].…”
Section: Discussionmentioning
confidence: 99%
“…Aseptic liver abscesses have been described in inflammatory bowel disease, particularly Crohn's, but are rare in systemic inflammatory conditions [9]. Maeshima et al reported a case of aseptic abscesses in a patient with Behcet's disease that improved with corticosteroid therapy [10,11]. The diagnosis of Behçet's was considered based on her reported painful oral and vaginal lesions but similar lesions in SLE have also been reported [12].…”
Section: Discussionmentioning
confidence: 99%
“…Among adults, AAs accompanied by BD are also rarely reported. A case was recently reported in which multiple abscesses were observed in the liver and spleen 12. The steroid dosage was increased when the condition recurred after initial steroid tapering, and the AAs eventually improved.…”
Section: Discussionmentioning
confidence: 99%
“…A case was recently reported in which multiple abscesses were observed in the liver and spleen. 12 The steroid dosage was increased when the condition recurred after initial steroid tapering, and the AAs eventually improved. However, there have been no reports of AAs associated with BD in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few cases of aseptic abscesses in BD successfully treated with corticosteroid therapy have been described. 3 Although this condition is an uncommon manifestation of BD, it is important for physicians to be aware of this possibility to avoid any delay in diagnosis and unnecessary medical and surgical measures.…”
Section: Answer To: Image 4 (Page 495): Multiple Aseptic Abscesses Ofmentioning
confidence: 99%